Qualidade da farinha de trigo de grão inteiro em resposta a influência de diferentes tamanhos de partículas - Bressiani, Joseane (2016)
The popularity of whole grain wheat flour (WGWF) isgrowing with the continuous research of the benefits of whole grains to health, its composition rich in vitamins, minerals, antioxidants and nutrientes that caracterizes as a functional food. Despite the health benefits, adverse effects on the rheological behavior of the mass and bakery products based on the WGWF are observed due to the presence of componentes of the germ and outer parts of the grain. The grinding process for its production is still a challenge for the industry, several techniques have been used resulting in wholemeals with different particle sizes and features. In this study, the goal was to prepare samples of WGWF with different particle sizes (thick, medium and fine) and evaluate the technological quality. For this purpose, differences in chemical composition, rheology, paste and microstructure were investigated and related to the mass properties and baking. The experiment was designed as entirely casualizad with four treatments and analysis in triplicate, except the microstructure. The significance of the data was tested by analysis of variance and the comparedmedia by Tukey test at 95% confidence interval. The results showed interference on the quality of bread caused by the particle size of WGWF. The effects observed as breads firmer and less volume compared to refined wheat flour (RWF) were related to the quality of the gluten network. The thick particles had longer development in the mass and less resistance to extension, indicating the formation of less cohesive gluten network. In the sample of fine particles, the most pronounced effects technological quality compared to the sample medium particle, suggested that the biggest surface contact and the biggest release of reactivecompounds with reducing characteristics due to cell rupture, interact with proteins forming gluten changing its functionality. The microstructure analysis shows that samples WGWF have submitted lower cohesion of the protein's network from the RWF. Quantification of free sulfhydryl groups of WGWF samples, added to the effects observed in mass and form bread indicates that particle size influences differently gluten network functionality. This study demonstrated the important relation between the particle size of WGWF and the mass properties and bakery. The particle size reduction strategies flour used to minimize the effects caused by the outer layers of the grain should be further investigated to optimize the preparation of bakery products. From the point nutritional view, smaller particles can assist in the release of bioactive compounds with actions, which act as antioxidants.